VIRTUAL REALITY-BASED SCULPTURE EDUCATION FRAMEWORKS - Tamilarasan S, Salai; Gupta, Suhas; Khalique, Fehmina; Kumar, R. Thanga; Arora, Mithhil; Lalitchandra, Mistry Roma; Panigra, Abhijeet; Korwar, Ganesh (ShodhKosh: Journal of Visual and Performing Arts, 2025)
With the emergence of Virtual Reality (VR) technologies, the field of sculpture education has gained the opportunity to overcome the limitations of physical materials, studio environment, and conventional teaching structures. The proposed paper suggests a cohesive VR-based Sculpture Education Framework consisting of the combination of immersive tools and the recognized sculptural practices to improve learning of creativity, development of technical skills, and a sense of engagement among learners. The research design includes a mixed-methods approach involving the examination of how VR platforms can be used to implement experiential learning, encourage learners to experiment, and expand the availability of sculptural processes to various learners. The participants (art students and educators) were invited to use a selected VR sculpting tools to complete modelling tasks, familiarize themselves with a three-dimensional form and reflect on the creative working process. The gathered information was used to compare the effectiveness of VR-based learning rooms in terms of their pedagogical efficiency using observations, interviews, and performance measures. The research results prove that VR improves the level of spatial knowledge, promotes riskless exploration, and allows quick prototyping, thus supplementing the practice of conventional sculpture but not eliminating it. The fundamental elements of the suggested conceptual framework include immersive interaction, the possibility of haptic feedback, multimodal guidance, and pathways of scaffolded learning. In addition to that, the research mentions effective pedagogical practices, such as guided discovery, iterative processes of modelling, hybrid learning methods that integrate physical and virtual learning. The assessment metrics of assessing the performance of learners, creative action, and technological fluency are also described.